Role Social Media in Enhancing Accounting Information System Effectiveness and Organizational Performance in Tapanuli Hotels - Maulana Siregar; Iskandar Muda Damanik; Sambas Ade Kesuma (Harmoni Economics: International Journal of Economics and Accounting, 2026)
This study aims to analyze the role of social media in improving the effectiveness of Accounting Information Systems (AIS) and organizational performance in hotel companies in South Tapanuli using the Resource-Based View (RBV) perspective. Within the RBV framework, innovation and knowledge sharing are viewed as strategic organizational resources that can influence AIS effectiveness and ultimately impact organizational performance. This study employed a quantitative approach with a survey method. Data were collected through questionnaires distributed to managers, owners, and the accounting, information technology, and operational divisions of hotels in South Tapanuli. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that innovation has no significant effect on Accounting Information System effectiveness. Conversely, knowledge sharing has a positive and significant effect on Accounting Information System effectiveness. Furthermore, Accounting Information System effectiveness has been shown to have a positive and significant effect on organizational performance. The R-square value indicates that variation in AIS effectiveness is largely explained by innovation and knowledge sharing, while the contribution of AIS effectiveness to organizational performance is relatively small compared to other factors outside the research model. These findings indicate that knowledge sharing practices are a dominant factor in increasing the effectiveness of Accounting Information Systems, which in turn impacts the performance of hotel organizations in South Tapanuli. Therefore, hotel companies need to strengthen their knowledge-sharing culture and optimize the use of information systems to support competitiveness and organizational goals.